2017
DOI: 10.1038/ncb3541
|View full text |Cite
|
Sign up to set email alerts
|

Lgr5-expressing chief cells drive epithelial regeneration and cancer in the oxyntic stomach

Abstract: The daily renewal of the corpus epithelium is fuelled by adult stem cells residing within tubular glands, but the identity of these stem cells remains controversial. Lgr5 marks homeostatic stem cells and 'reserve' stem cells in multiple tissues. Here, we report Lgr5 expression in a subpopulation of chief cells in mouse and human corpus glands. Using a non-variegated Lgr5-2A-CreERT2 mouse model, we show by lineage tracing that Lgr5-expressing chief cells do not behave as corpus stem cells during homeostasis, bu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

17
307
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 223 publications
(328 citation statements)
references
References 42 publications
17
307
0
4
Order By: Relevance
“…To induce injury in the stomach, we employed a high-dose tamoxifen ("HD-Tam") injury model that has been used by us and others (Huh et al, 2012;Burkitt et al, 2017;Lee et al, 2017;Leushacke et al, 2017). HD-Tam causes loss of nearly all acid-secreting parietal cells in the body of the stomach (Figs EV1 and EV3) and induces mature, differentiated digestive-enzyme-secreting chief cells at the base of the unit to give rise to a proliferating cell population (Radyk et al, 2018).…”
Section: Diverse Organs Show Similar Changes In Metabolic Activity Dumentioning
confidence: 99%
“…To induce injury in the stomach, we employed a high-dose tamoxifen ("HD-Tam") injury model that has been used by us and others (Huh et al, 2012;Burkitt et al, 2017;Lee et al, 2017;Leushacke et al, 2017). HD-Tam causes loss of nearly all acid-secreting parietal cells in the body of the stomach (Figs EV1 and EV3) and induces mature, differentiated digestive-enzyme-secreting chief cells at the base of the unit to give rise to a proliferating cell population (Radyk et al, 2018).…”
Section: Diverse Organs Show Similar Changes In Metabolic Activity Dumentioning
confidence: 99%
“…It is known that LGR5 + cells with properties of self-renewal are located in the gastric antrum and yield long-lived gastric units in vitro 77 . Furthermore, reserve LGR5 + cells have now been identified within mouse and human chief cells and can catalyse epithelial regeneration after injury in vitro 78 . Although LGR5 + cells do not appear to give rise to either SPEM 79 or intestinal metaplasia, they have been found to give rise to early gastric cancer 78 .…”
Section: Cell Of Originmentioning
confidence: 99%
“…While one group has suggested that SPEM arises from isthmal progenitor cells in the corpus [57], the vast majority of evidence from multiple groups indicates that chief cells are indeed the predominant origin of SPEM lineages in the stomach corpus. [42,47,56,5860] Importantly, expression of pepsinogen I has been used as a marker of pseudopyloric metaplasia [61], consistent with the equivalence of pseudopyloric metaplasia with SPEM. Similarly, ductal metaplasia/PanIN lesions in the pancreas appear to evolve from reprogramming of zymogen-secreting pancreatic acinar cells [62].…”
Section: Lineage Origins Of Pyloric-type Reparative Mucous Cellsmentioning
confidence: 99%